Cost of crime: A systematic review. Issue 3 (May 2015) - Wickramasekera, Nyantara; Wright, Judy; Elsey, Helen; Murray, Jenni; Tubeuf, Sandy
Abstract Purpose This study aims to systematically search and review all the relevant studies that have estimated the cost of crime of adult offenders. Methods Fifteen databases were searched for published studies and grey literature. We included studies that estimated the cost of crime of adult offenders. Due to high heterogeneity results were synthesised descriptively. Results Twenty-one studies estimated the cost of crime. There was considerable variance in the estimated total costs of crime and studies from the United States consistently reported the highest total costs. All the studies consistently included robbery and burglary in the total cost estimate. Homicide was ranked as the most costly offence and accounted on average for 31% of the total cost of crime, followed by drug offence (21%) and fraud (17%). Crime categories that involved violence to a person were associated with large intangible costs. Conclusions While it is difficult to precisely determine what caused the large variance in the total cost estimates, we think that it could be due to changes in unit costs, changes in crime trends, and variations in the methods used to estimate costs. The findings from this systematic review highlight the need for more up-to-date studies with better reporting standards.